Ikan Mas sebagai Ide Penciptaan Batik Tulis dengan Memadukan Ornamen Mandailing pada Pembuatan Hiasan Dinding - Pebrina Sari Rambe; Wahyu Tri Atmojo; Raden Burhan Surya Nata Diningrat (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
This research aims to explore the visual potential of the goldfish as a source of inspiration in the creation of hand-drawn batik works by incorporating traditional Mandailing ornaments. The goldfish was selected due to its strong symbolic meaning in local culture, representing luck, prosperity, and happiness. Meanwhile, Mandailing ornaments rich in philosophical and aesthetic cultural values serve as supporting elements that strengthen the visual identity of the work. The creative method used in this study follows the approach proposed by Husen Hendriyana, consisting of four stages: preparation, imagination (exploration), development of imagination (design), and realization (execution). The creative process involves illustrating the form of the goldfish combined harmoniously with distinctive Mandailing motifs such as bona bolu, bindu pusuk ni robung, burangir/aropik, sipatomu-tomu, bintang na toras, rudang, raga-raga, sancang duri, jagar-jagar, bondul na opat, tagan, bintang dohot tolu lingkaran, timbangan, podang, gancip, takar, pinggan, mataniari, horis, loding/upak, bintang, alaman bolak, parbincar mataniari, gimbang, lotus flower, and gumbot. The outcome of this research consists of 12 hand-drawn batik artworks applied as wall decorations using a contemporary approach. These works function both aesthetically and educationally, as well as decoratively. The artworks are expected to contribute to the development of hand-drawn batik as a visual art form that adapts to modern times, while also promoting and preserving the rich cultural heritage of the Mandailing through a broader visual format.